Addressing Adversities in Caring for Mental Health in Rural Settings: A Conversation with Rural Mental Healthcare Practice Co-founder Dr. Taryn S. Van Gilder-Pierce - Nahian, Ahmed; Shepherd, Jewel; Van Gilder-Pierce, Taryn S. (International Journal of Medical Students, 2023)
Due to lack of mental healthcare facilities in rural areas, the population often resorts to private practice practitioners to address their need for mental health services. Dr. Taryn S. Van Gilder-Pierce and her husband, Dr. William D. Pierce founded their private practice in Yankton, SD in 2001. She has more than 25 years of training and experience treating individuals, married couples, families, and groups in rural South Dakota. The interview delves into the challenges faced by early career professionals in building a practice in remote areas and extends into the room for expansion within the field of rural mental health provision of services.